2019
DOI: 10.1101/668327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifactorial motor behavior assessment for real-time evaluation of emerging therapeutics to treat neurologic impairments

Abstract: Conflict of interestThe authors declare no conflicts of interest. AcknowledgementsThe authors thanks Mr. Seungleal (Brian) Paek for surgical and experimental assistance related to the Parkinsonian model. Finally, the authors thank Mayo Clinic's Division of Engineering for their support to design and construct the multifactorial assessment system. AbstractIntegrating multiple assessment parameters of motor behavior is critical for understanding neural activity dynamics during motor control in both intact and dy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…4 week time-point in this study of the combined therapy group (5.29±0.7) was similar to effect of OPF+ scaffolds with GDNF Schwann cells (3.67±0.4) 13 . Limitations of BBB 40,41 we added to the validity of these findings with electrophysiological and kinematic analysis in behavior assessment system 42 . Improvement in group with combined therapy vs. EES only, and with intermediate effect in scaffolds only group was found.…”
Section: Figure 4 About Herementioning
confidence: 99%
See 3 more Smart Citations
“…4 week time-point in this study of the combined therapy group (5.29±0.7) was similar to effect of OPF+ scaffolds with GDNF Schwann cells (3.67±0.4) 13 . Limitations of BBB 40,41 we added to the validity of these findings with electrophysiological and kinematic analysis in behavior assessment system 42 . Improvement in group with combined therapy vs. EES only, and with intermediate effect in scaffolds only group was found.…”
Section: Figure 4 About Herementioning
confidence: 99%
“…Nexus system was used to obtain threedimensional coordinates of the markers. Analysis of kinematic data was performed using method previously described 42 .…”
Section: Spinal Cord Electrical Epidural Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of effective single clinical therapeutic to heal the human spinal cord following injury lead to multiple state-of-the-art combinatorial treatment paradigms that demonstrate functional gains below the level of SCI. Numerous preclinical investigations, as well as a few clinical trials, have reported beneficial outcomes from experimental treatments, such as immunomodulatory therapies (Krupa and others 2019; Machova Urdzikova and others 2015), stem cells (Islamov and others 2017; Izmailov and others 2017; Krupa and others 2018; Mukhamedshina and others 2019; Ruzicka and others 2017), trophic factors (Zhang and others 2014), electrical stimulation (ES) of the sublesional spinal cord circuits (Gerasimenko and others 2001; Gill and others 2018; Ichiyama and others 2005a; Islam and others 2019b; Lavrov and others 2015), or neuroprosthetics approaches (Frigon and others 2011; Mikhaylov and others 2020; Shah and Lavrov 2017).…”
Section: Introductionmentioning
confidence: 99%